HYPERENDEMIC FASCIOLIASIS ASSOCIATED WITH SCHISTOSOMIASIS IN VILLAGES IN THE NILE DELTA OF EGYPT - ESTEBAN, JOSE-GUILLERMO; GONZALEZ, CAROLINA; CURTALE, FILIPPO; MUNOZ-ANTOLI, CARLA; VALERO, MARIA ADELA; BARGUES, MARIA DOLORES; EL SAYED, MABROUK; EL WAKEEL, ALY A. W; ABDEL-WAHAB, YEHIA; MONTRESOR, ANTONIO; ENGELS, DIRK; SAVIOLI, LORENZO; et al. (The American journal of tropical medicine and hygiene, 2003)
Coprologic surveys were carried out in villages of the Behera Governorate in the Nile Delta region of Egypt to characterize the epidemiologic features of human fascioliasis caused by Fasciola hepatica and F. gigantica in this lowland endemic area by comparison with fascioliasis caused by only F. hepatica in areas hyperendemic for human disease in the Andean highlands of South America. The fascioliasis prevalences detected (range = 5.2–19.0%, mean = 12.8%) are the highest obtained in Egypt. The comparison with previous results suggests that in the Nile Delta, fascioliasis is spreading from an original situation of sporadic human cases in well-known endemic foci for animal disease to an endemic distribution in humans, which may be characterized as a mesoendemic region that includes several hyperendemic areas for human disease. As in Andean countries, a relationship with sex was found, although in Egypt prevalences, but not intensities, appeared to be significantly higher in females. All ages appear to be susceptible to liver fluke infection, with prevalences and intensities being lower before and after school age, a situation that is consistent with that detected in Andean countries, although the peak in the 9–11-year-old age group appears less pronounced in Egypt. The intensities were very high when compared with those found in subjects sporadically infected in areas endemic for animal disease, but relatively low for a hyperendemic situation, although the intensities may not be conclusive because of the transmission seasonality of fascioliasis in the Nile Delta. The marked similarities in the qualitative and quantitative spectrums of protozoans and helminths, multiparasitisms, and associations between liver flukes and other parasitic species suggest physiographic-hydrographic and behavioral-social characteristics similar in all areas hyperendemic for human fascioliasis, which are independent of other factors such as climate, altitude, and cultural or religious features. The significant positive association between liver fluke infection and schistosomiasis mansoni detected in one locality has never been described elsewhere, and must be considered relevant from clinical, pathologic, diagnostic, and therapeutic points of view. Interestingly, the relationships of schistosomiasis prevalences and intensities with sex and age follow patterns similar to those found in fascioliasis.